Perfil do conhecimento/percepção de HIV/AIDS entre gestantes. - Vieira, Renata Braga Rolim (2016)
Introduction: AIDS is considered a chronic disease and, nowadays, approximately 36.9 million people with the disease live in the world. In Brazil, since the beginning of the epidemic to the present day, 798,366 AIDS cases have been reported. In pregnant women, the HIV detection rate showed an upward trend over the past decade. Objective: to analyze the knowledge of HIV / AIDS, according to sociodemographic characteristics of pregnant women in the city of Sousa- PB. Methodology: This was a cross sectional study with a quantitative approach, conducted with 164 pregnant women, stratified by 26 basic health units in the city of Sousa-PB. The dependent variable was the knowledge about HIV / AIDS and as independent variables sociodemographic characteristics (age, socioeconomic classification, marital status, education, religion, race / color and working condition). The variables were described as frequencies and proportions. The differences among proportions were analyzed using the chi-square tests of Pearson and Fisher exact. Results: Based on the results, the profile of the study participants were pregnant women with a mean age of 26.13 years, most of them married, with incomplete elementary school, mulatto, religious (Catholic) and unemployed. It was found that, regarding HIV prevention, 74.4% considered that sexual intercourse with faithful and uninfected partner reduces the risk of HIV, 60.4% agreed that pregnant women with proper treatment prevents vertical HIV transmission and 62.2% believed appropriate treatment does not reduce risk of horizontal transmission. Age and education enhanced that older pregnant women, with higher education level showed increased knowledge on HIV / AIDS. Conclusion: There are gaps in knowledge on the vertical and horizontal transmission of the interviewed mothers. More effective measures to promote sex education in schools, universities and communities, emphasizing the importance of practicing safe sex, knowledge for the prevention and transmission of HIV are extremely necessary, as well as prenatal care quality, to increase knowledge among the general population and, thus, decrease the number of cases of HIV / AIDS in Brazil and worldwide.